2023
DOI: 10.1021/acsabm.2c00952
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of MG-63 Osteogenic Response on Mechano-Bactericidal Micronanostructured Titanium Surfaces

Abstract: Despite recent advances in the development of orthopedic devices, implant-related failures that occur as a result of poor osseointegration and nosocomial infection are frequent. In this study, we developed a multiscale titanium (Ti) surface topography that promotes both osteogenic and mechanobactericidal activity using a simple two-step fabrication approach. The response of MG-63 osteoblast-like cells and antibacterial activity toward Pseudomonas aeruginosa and Staphylococcus aureus bacteria was compared for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…For instance, the combination of micro/nanostructures was expected to create a biological synergy that can further enhance osteoblast behavior. 40 By the introduction of wellestablished nanostructures, certain nanostructures have exhibited suitable conditions for different types of cells to grow. These topographies apply mechanical forces to a flat interface that attaches cells and causes them to elongate and differentiate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the combination of micro/nanostructures was expected to create a biological synergy that can further enhance osteoblast behavior. 40 By the introduction of wellestablished nanostructures, certain nanostructures have exhibited suitable conditions for different types of cells to grow. These topographies apply mechanical forces to a flat interface that attaches cells and causes them to elongate and differentiate.…”
Section: Introductionmentioning
confidence: 99%
“…Cell adhesion behavior is a complex phenomenon intertwined with several interface factors, encompassing parameters such as roughness ratios, wettability, and chemical attributes. For instance, the combination of micro/nanostructures was expected to create a biological synergy that can further enhance osteoblast behavior . By the introduction of well-established nanostructures, certain nanostructures have exhibited suitable conditions for different types of cells to grow.…”
Section: Introductionmentioning
confidence: 99%
“…23 Furthermore, similar nanostructured surfaces have shown excellent cytocompatibility with human macrophage, 23 fibroblast cells, 21 and osteoblast-like cells. 24 Recently, an in vivo sheep model study compared implants having surfaces modified with antibacterial nanostructures to the gold standard hydroxylapatite-coated devices. The study reported enhanced bone integration with the antibacterial nanostructured implants.…”
Section: Introductionmentioning
confidence: 99%
“…For titanium nanostructures, a common and facile method for nanostructure fabrication is hydrothermal etching (HTE). , HTE titanium (HTE-Ti) nanostructures have been shown to be effective against both fungi and bacteria (Gram-positive and Gram-negative) , for an extended period of time . Furthermore, similar nanostructured surfaces have shown excellent cytocompatibility with human macrophage, fibroblast cells, and osteoblast-like cells . Recently, an in vivo sheep model study compared implants having surfaces modified with antibacterial nanostructures to the gold standard hydroxylapatite-coated devices.…”
Section: Introductionmentioning
confidence: 99%